Mimicry and affective disorders - Salazar Kämpf, Maike; Kanske, Philipp (Frontiers in Psychiatry, 2023)
Mimicry, the spontaneous imitation of an interaction partner, is an important part of everyday communication, as it has been shown to foster relationships and increase closeness. People with affective disorders often have problems in their interpersonal lives. In this review, we pursue the question if these problems are linked to differences in mimicry behavior. First, we summarize existing evidence on mimicry, depression and mood. Then, based on five theories differing in their core assumptions regarding mechanisms and functionality of mimicry, we derive suggestions on how mimicry might affect people suffering from bipolar disorders, dysthymia or depression. Depending on each theory, a different understanding of affective disorders and mimicry arises, and we show how the evidence fit in with the suggested theories. Previous studies on affective disorders have focused on mimicry behavior of participants watching photos, computer-generated images, or short video sequences. This review sheds light on the fact that evidence on mimicry needs to be broadened systematically for people with affective disorders in interactional settings. Mimicry represents a novel and important yet underestimated source for diagnostic, intervention and evaluation processes in affective disorders.